Fauna insectil asociada a cultivos de dos especies de Physalis (Solanaceae) en Argentina - Bado, S.G.=700 1 Cerri, A.M.; Vilella, F.
(En, Es)
ilus., 18 ref.
Keywords: PHYSALIS PERUVIANA; PHYSALIS IXOCARPA; SOLANACEAE; SOLANACEAE; IDENTIFICACION; INSECTA; DAÑOS; MANEJO DEL CULTIVO; ESPAÑA